The Effect Of Giving Earth Worms ( Lumbricus Rubellus ) As A Substitute For Antibiotic Growth Promotor (AGP) On The Performance Of Ayam Kampong Super In Infection Salmonella Sp - Rizky, Adrian; R.E. Mirwandhono; K. Cendekia; L. Prayitno (Talenta Publisher, 2023)
Study This was held in Jalan Lizardi Putra No. 17 district. Lucky Field from month January 2022 to February 2022. Research This aims To learn to use flour worm ground ( Lumbricus rubella ) as an additive in feed to performance ( add body weight (PBB), consumption feed, and conversion feed super free range chicken The material used in the research This is 150 days old super free -range chickens ( DOC/ Day Old Chicken ) and maintained for 60 days. Treatment of the feed given to the study This includes P0 Control ( No infection ); P 1: Without Antibiotics + Infection ; P 2: Antibiotics Trimizyn -s + Infection ; P 3: 50 mg/kg Flour Earthworms + Infection ; P 4: 100 mg/kg Flour Earthworm + Infection. Study This uses a design random complete (RAL) pattern in the same direction with 5 (five) treatments and 6 ( six ) repetitions, where every test contains 5 (five) tails of chicken. Results show that the average consumption ratio (g/head/week) P0, P1, P2, P3, and P4 was 322.18; 303.97; 310.57; 313.80, and 315.09, increments body weight (g/ head ) was 821.92; 712.71; 777.08; 773.49 and 780.87 and conversion rations is 3.50; 3.52; 3.85; 3.57 and 3.74. From research, This can be concluded that flour worm land is capable replace Antibiotic Growth Promoter (AGP) in rations of free-range chicken